2020
DOI: 10.4315/jfp-20-146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Escherichia coli O157:H7 on Pork Carcasses and in Swine Colon Contents from Provincially Licensed Abattoirs in Alberta, Canada

Abstract: The objective of this study was to determine the prevalence of Shiga toxin-producing E. coli (STEC) O157:H7 in colon content and on carcasses from pigs slaughtered at provincially licensed abattoirs (PLAs) in Alberta. In 2017, carcass sponge samples and colon content samples were collected from 504 healthy market hogs at thirty-nine PLAs and analyzed for E. coli O157:H7. Carcass samples were also analyzed for generic E. coli and aerobic colony count (ACC). Of the 504 carcass samples, nine were confirmed positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Early studies pointed out that a high rate of O157 STEC was found in ground meat (beef and pork) originating from Calgary, Alberta, Canada (25). Following three O157 STEC outbreaks in Alberta, Canada, that were associated with ground pork, a focused study was conducted in which O157 STEC was isolated from 7 (1.4%) of 504 swine colon fecal samples from healthy market swine of Albertan farms (27). Other studies have also detected O157 STEC in swine colon fecal samples obtained at slaughter facilities in the United States (32).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies pointed out that a high rate of O157 STEC was found in ground meat (beef and pork) originating from Calgary, Alberta, Canada (25). Following three O157 STEC outbreaks in Alberta, Canada, that were associated with ground pork, a focused study was conducted in which O157 STEC was isolated from 7 (1.4%) of 504 swine colon fecal samples from healthy market swine of Albertan farms (27). Other studies have also detected O157 STEC in swine colon fecal samples obtained at slaughter facilities in the United States (32).…”
Section: Discussionmentioning
confidence: 99%
“…It was unclear whether the E. coli O157 isolates in the pork products were pig-adapted strains or due to cross-contamination from cattle. A surveillance study (23) and outbreak-related investigations recovered Shiga toxin gene-containing O157:H7 from pig fecal samples and pork production environments in Alberta. This study sequenced the genomes of these isolates and O157:H7 isolated from cattle in Alberta to identify the potential source of O157:H7 contaminating pork.…”
mentioning
confidence: 99%
“…This study sequenced the genomes of these isolates and O157:H7 isolated from cattle in Alberta to identify the potential source of O157:H7 contaminating pork. These isolates included E. coli O157:H7 recovered from pigs (n = 41; Pig01 to Pig41), pork production-related environments (n = 25; Env01 to Env25), and cattle (n = 38; Cat01 to Cat12, Cat14 to Cat19, Cat21 to Cat23, and Cat25 to Cat41) in Alberta, Canada (23)(24)(25)(26)(27)(28)(29) (Table 1). Pig isolates were recovered from either the cecal contents of pigs in pork processing facilities or pig feces from barns (23).…”
mentioning
confidence: 99%
See 2 more Smart Citations